2010
DOI: 10.1093/mutage/geq028
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and 8-oxoguanine repair are enhanced in colon adenoma and carcinoma patients

Abstract: Oxidative stress is involved in the pathogenesis of colon cancer. We wanted to elucidate at which stage of the disease this phenomenon occurs. In the examined groups of patients with colorectal cancer (CRC, n = 89), benign adenoma (AD, n = 77) and healthy volunteers (controls, n = 99), we measured: vitamins A, C and E in blood plasma, 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) and 8-oxo-7,8-dihydroguanine (8-oxoGua) in leukocytes and urine, leukocyte 8-oxoGua excision activity, mRNA levels of APE1, OGG1, 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 51 publications
7
67
0
3
Order By: Relevance
“…3), enabling the activation of NLRP3 in signal II (43,44). Acrolein-mediated transcription silencing by promoter methylation of OGG1 resulted in reduced capacity to repair 8-oxo-dG (28,31,32). Activated NLRP3 can stimulate the complex with apoptosis-associated speck-like protein containing CARD (ASC) to cause the proteolytic maturation of caspase-1 (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), enabling the activation of NLRP3 in signal II (43,44). Acrolein-mediated transcription silencing by promoter methylation of OGG1 resulted in reduced capacity to repair 8-oxo-dG (28,31,32). Activated NLRP3 can stimulate the complex with apoptosis-associated speck-like protein containing CARD (ASC) to cause the proteolytic maturation of caspase-1 (45).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinamide reactivated only three base excision repair genes, Neil1 (p value Ͻ 0.01), Ogg1 (p value Ͻ 0.05), and Parp1 (p value Ͻ 0.01), as well as a homologous recombination repair gene, Rad50 (p value Ͻ 0.001). The epigenetic silencing of Ogg1, responsible for mitochondrial DNA damage repair, could support the accumulation of 8-oxo-dG for associated NLRP3-mediated caspase 1 activation (28,31,32).…”
Section: Bladder Inflammation Causes Detrusor Cell Death Andmentioning
confidence: 99%
“…Interestingly, we found that OGG1 rs1052133-GG was associated with early age of lung cancer onset. Some studies examining the relationship between the OGG1 Ser326Cys genotype and BER repair activity or OGG1 expression have revealed that the OGG1 Ser326Cys polymorphism is not associated with differences in repair capacity or OGG1 expression (Janssen et al, 2001(Janssen et al, , 2012, whereas other studies have reported that the Ser326Cys genotype causes substantially decreased repair activity or higher mRNA levels of OGG1 (Vodicka et al, 2007;Hatt et al, 2008;Obtulowicz et al, 2010). Thus, based on the literature, we cannot draw conclusions regarding the association between the OGG1 Ser326Cys polymorphism and the level of DNA damage and repair capacity of BER in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, conflicting results have been reported for the association of the XRCC1 Arg399Gln polymorphism and lung cancer risk (Zhou et al, 2003;Popanda et al, 2004;Matullo et al, 2006;Ryk et al, 2006). Similarly, inconclusive results have been obtained for the OGG1 Ser326Cys polymorphism regarding its association with cancer (Janssen et al, 2001;Vodicka, et al, 2007;Hatt et al, 2008;Obtulowicz et al, 2010;Jensen et al, 2012). In addition, little is known regarding the relationship between the PARP1 rs1136410 (Val762Ala) polymorphism and lung cancer risk (Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer patients, the level of vitamin A, vitamin C, and vitamin E were reduced, and urinary 8-oxo-dG, a biomarker of DNA oxidation, was elevated (Obtulowicz et al, 2010).…”
Section: Vitamins (Except Vitamin D)mentioning
confidence: 99%